Learning the assessment protocol through the framework of teaching for understanding - Cifuentes-Garzón, José Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article reports the findings of a study whose objective was to analyze the incidence of a didactic unit designed in the framework of Teaching for Comprehension (Teaching for Comprehension (Teaching for Comprehension), in the learning of the assessment protocol in teachers of basic secondary education. A qualitative approach research was chosen, with the pedagogical action research design, carried out with the participation of 10 teachers from a Colombian public educational institution. The instruments used were: the thinking routine "before I thought ... now I think", the research workshop and the assessment protocol. The results show that, with the implementation of the moments of the exploration of the topic, the guided research and the final synthesis project, the teachers learned and applied the assessment protocol. It is concluded that the transfer to the classroom practices of the EpC and the evaluation protocol are opportunities for the improvement of the processes of evaluation of the learning in students, at the same time that they allow to refine the processes of planning of classes in the teachers.